2009
DOI: 10.1111/j.1365-2052.2009.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure in peripheral dog breeds: Portuguese native breeds as a case study

Abstract: Genetic variability in purebred dogs is known to be highly structured, with differences among breeds accounting for approximately 30% of the genetic variation. However, analysis of the genetic structure in non-cosmopolitan breeds and local populations is still limited. Nine Portuguese native dog breeds, and other peripheral dog populations (five) with regional affinities, were characterized using 16 microsatellites and 225 amplified fragment length polymorphism (AFLP) markers, and the pattern of genetic differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 48 publications
2
19
0
2
Order By: Relevance
“…As a result of these mating practices, we found that 28% of the dogs with American pedigree were genetically classified as Europeans. Our findings are in agreement with recent studies, which support up to 30% of genetic variation in pure breeds [22]. This genetic variation can cause important genetic differences even among different countries as Quingnon and colleagues point out [23].…”
Section: Discussionsupporting
confidence: 94%
“…As a result of these mating practices, we found that 28% of the dogs with American pedigree were genetically classified as Europeans. Our findings are in agreement with recent studies, which support up to 30% of genetic variation in pure breeds [22]. This genetic variation can cause important genetic differences even among different countries as Quingnon and colleagues point out [23].…”
Section: Discussionsupporting
confidence: 94%
“…Microsatellite and AFLP analyses of modern dog suggest that the genetic variability of dog breeds is structured according to breeds and geography (Pires et al, 2009) and that Portuguese dogs have multiple mtDNA haplotypes in agreement with the mtDNA diversity found in other European dogs (Pires et al, 2006).…”
supporting
confidence: 60%
“…In the Iberian Peninsula, both dog and wolf subspecies have been the focus of several studies where molecular markers were used to describe genetic composition, population structure, and phylogeny. Microsatellite and AFLP analyses of modern dog suggest that the genetic variability of dog breeds is structured according to breeds and geography (Pires et al., ) and that Portuguese dogs have multiple mtDNA haplotypes in agreement with the mtDNA diversity found in other European dogs (Pires et al., ).…”
Section: Introductionmentioning
confidence: 72%
“…The Bayesian Clustering Algorithms can identify further substructure by re‐analysing the identified clusters following an approach used in Pires et al. (2009) and Bray et al.…”
Section: Methodsmentioning
confidence: 99%